A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial of Preoperative Antithrombin Supplementation in Patients at Risk for Antithrombin Deficiency After Cardiac Surgery. (25th July 2022) - Moront, Michael George; Woodward, Michael K.; Essandoh, Michael K.; Avery, Edwin G.; Reece, T. Brett; Brzezinski, Marek; Spiess, Bruce; Shore-Lesserson, Linda; Chen, Junliang; Henriquez, Waleska; Barceló, Miquel; Despotis, George; et al.
Abstract : BACKGROUND: Antithrombin (AT) activity is reduced during cardiac operations with cardiopulmonary bypass (CPB), which is associated with adverse outcomes. Preoperative AT supplementation, to achieve >58% and <100% AT activity, may potentially reduce postoperative morbidity and mortality in cardiac operations with CPB. This prospective, multicenter, randomized, double-blind, placebo-controlled study was designed to evaluate the safety and efficacy of preoperative treatment with AT supplementation in patients at risk for low AT activity after undergoing cardiac surgery with CPB. METHODS: A total of 425 adult patients were randomized (1:1) to receive either a single dose of AT (n = 213) to achieve an absolute increase of 20% above pretreatment AT activity or placebo (n = 212) before surgery. The study duration was approximately 7 weeks. The primary efficacy end point was the percentage of patients with any component of a major morbidity composite (postoperative mortality, stroke, acute kidney injury [AKI], surgical reexploration, arterial or venous thromboembolic events, prolonged mechanical ventilation, and infection) in the 2 groups. Secondary end points included AT activity, blood loss, transfusion requirements, duration of intensive care unit (ICU), and hospital stays. Safety was also assessed. RESULTS: Overall, 399 patients (men, n = 300, 75.2%) with a mean (standard deviation [SD]) age of 66.1 (11.7) years, with the majority undergoing complex surgical procedures (n = 266, 67.9%), were analyzed. No differences in the percentage of patients experiencing morbidity composite outcomes between groups were observed (AT-treated 68/198 [34.3%] versus placebo 58/194 [29.9%]; P = .332; relative risk, 1.15). After AT infusion, AT activity was significantly higher in the AT group (108% [42–143]) versus placebo group (76% [40–110]), and lasted up to postoperative day 2. At ICU, the frequency of patients with AT activity ≥58% in the AT group (81.5%) was significantly higher ( P < .001) versus placebo group (43.2%). Secondary end point analysis did not show any advantage of AT over placebo group. There were significantly more patients with AKI ( P < .001) in the AT group (23/198; 11.6%) than in the placebo group (5/194, 2.6%). Safety results showed no differences in treatment-emergent adverse events nor bleeding events between groups. CONCLUSIONS: AT supplementation did not attenuate adverse postoperative outcomes in our cohort of patients undergoing cardiac surgery with CPB.